TINDAK KEKERASAN ANAK MENGAKIBATKAN LUKA BERAT BERDASARKAN UU PERLINDUNGAN ANAK PUTUSAN 404/2020 - Simbolon, Meilin; Ika Darmika; Inri Januar (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
This purpose is to find out and analyze the regulations on child protection as acts of violence that result in serious injuries based on Law 35 of 2014. The research method used in this study is a normative juridical law research method with a law approach and a case approach. The data used are secondary data consisting of primary, secondary, and tertiary legal materials. Data analysis used qualitative analysis. The research method used in this research is a normative juridical legal research method with the law approach and case approach. The data used are secondary data consisting of primary, secondary, and tertiary legal materials. Data analysis used qualitative analysis. The results of the research from the case No.404/Pid.sus/2020/PN Jap, it turns out that from the results of the study, physical violence against children that resulted in serious injuries has been legally proven guilty wherein the judge decided that the defendant was obliged to pay court fees of 5000.00 (five thousand rupiah).